Predictors of fall protection motivation among older adults in rural communities in a middle-income country : A cross-sectional study using the Protection Motivation Theory - Ong, Mei Fong; Soh, Kim Lam; Rosalia, Saimon; Hasni Idayu, Saidi; Tiong, Ing Khieng; Myint, Wai Wai; Manfred, Mortell; Salimah, Japar (John Wiley & Sons Ltd., 2024)
Aims To evaluate factors associated with fall protection motivation to engage in fall preventive behaviour among rural community-dwelling older adults aged 55 and above using the protection motivation theory scale.